Prevalence and risk factors of MRI-defined brain infarcts among Chinese adults - Wu, Jing; Gao, Yongxiang; Malik, Vasanti; Gao, Xiang; Shan, Ruiqi; Lv, Jun; Ning, Yi; Wang, Bo; Li, Liming (Frontiers in Neurology, 2022)
Background Few studies have explored the prevalence and risk factors of brain infarcts (BI) detected by magnetic resonance imaging (MRI) in China. The purpose was to evaluate the prevalence and risk factors of brain infarcts (BI) detected by magnetic resonance imaging (MRI) in 1.4 million Chinese adults. Methods This was a multicenter cross-sectional study conducted on 1,431,527 participants aged ≥18 years (mean age: 46.4 years) who underwent MRI scans in health examinations from 28 provinces of China in 2018. MRI-defined BI was defined as focal parenchymal lesions ≥3 mm. Multivariable logistic regression analyses were performed to evaluate risk factors associated with MRI-defined BI. Results The age- and sex-standardized prevalence of MRI-defined BI, lacunar and non-lacunar infarcts were 5.79% (5.75–5.83%), 4.56% (4.52–4.60%), and 1.23% (1.21–1.25%), respectively. The sex-standardized prevalence of MRI-defined BI ranged from 0.46% among those aged 18–29 years to 37.33% among those aged ≥80 years. Men (6.30%) had a higher age-standardized prevalence of MRI-defined BI than women (5.28%). The highest age- and sex-standardized prevalence of MRI-defined BI was observed in the Northwest (8.34%) and Northeast (8.02%) regions, while the lowest prevalence was observed in the Southwest (4.02%). A higher risk of MRI-defined BI was associated with being male [odd ratio (OR) 1.17, 95% CI 1.15–1.19], older age (OR per 10-year increments 2.33, 2.31–2.35), overweight (1.12, 1.10–1.14) or obesity (1.18, 1.16–1.21), hypertension (1.80, 1.77–1.83), diabetes (1.24, 1.21–1.26), and dyslipidemia (1.07, 1.05–1.08). Conclusion MRI-defined BI is highly prevalent in China, even among young adults. MRI-defined BI was associated with being male, older age, living in the northern region, and metabolic conditions.